GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2085516 species occurrences available in GBIF matching the query: TaxonKey: Aves Country: Canada HasCoordinate: true Geometry: POLYGON((-82.441406 63.470144,-82.441406 43.197167,-51.503906 43.197167,-51.503906 63.470144,-82.441406 63.470144)) HasGeospatialIssue: false Year: 2001-2010. The dataset includes 2085516 records from 30 constituent datasets: 1191 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 3937 records from The avian collection at the Natural History Museum, Oslo, Norway. 700 records from Arctic Species Trend Index (ASTI) : Terrestrial. 10 records from Arctic Species Trend Index (ASTI) : Marine. 4 records from Museum of Comparative Zoology, Harvard University. 1802611 records from EOD - eBird Observation Dataset. 185 records from iNaturalist Research-grade Observations. 1629 records from naturgucker. 87 records from Macaulay Library Audio and Video Collection. 119818 records from Great Backyard Bird Count. 5990 records from Marsh Monitoring Program - Birds. 1099 records from Canadian Lakes Loon Survey. 122429 records from Ontario Breeding Bird Atlas 2001-2005. 1 records from Canadian Museum of Nature Bird Collection. 1 records from UWBM Ornithology Collection. 41 records from Atlantic Canada Conservation Data Centre (OBIS Canada). 5 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 232 records from NBM birds. 8521 records from Hawk Migration Association of North America - HawkCount. 1 records from MVZ Egg and Nest Collection (Arctos). 1788 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 565 records from Geographically tagged INSDC sequences. 4 records from SAFRING: Historical Bird Ringing Records (2005-2009). 5 records from Cowan Tetrapod Collection - Birds. 19 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 37 records from MVZ Bird Collection (Arctos). 100 records from Arctic Species Trend Index (ASTI) : Freshwater. 34 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 541 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 4 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences